2019
DOI: 10.1186/s13722-019-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic self-administered screening for substance use in adult primary care patients: feasibility and acceptability of the tobacco, alcohol, prescription medication, and other substance use (myTAPS) screening tool

Abstract: Background The TAPS Tool is a substance use screening and brief assessment instrument that was developed for use in primary care medical settings. It is one of the first screening instruments to provide rapid assessment of all commonly used substance classes, including illicit and prescription opioids, and is one of the only available screeners designed and validated in an electronic self-administered format (myTAPS). This secondary analysis of data from the TAPS Tool validation study describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
(53 reference statements)
4
18
0
Order By: Relevance
“…Two study clinics achieved rates of positive screening results for moderate- to high-risk alcohol use that exceeded general population estimates, and all 5 clinics using a self-administered approach detected a greater than 14% prevalence of moderate- to high-risk alcohol use (vs <2% for the clinic that used staff-administered screening). Our findings are consistent with those of previous studies using self-administered screening, which typically produces more accurate reporting among patients with stigmatized conditions . Our findings could also reflect problems with the quality of screening when administered by staff, who may change the wording of validated screening questions in an effort to hasten the process or reduce perceived patient discomfort …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two study clinics achieved rates of positive screening results for moderate- to high-risk alcohol use that exceeded general population estimates, and all 5 clinics using a self-administered approach detected a greater than 14% prevalence of moderate- to high-risk alcohol use (vs <2% for the clinic that used staff-administered screening). Our findings are consistent with those of previous studies using self-administered screening, which typically produces more accurate reporting among patients with stigmatized conditions . Our findings could also reflect problems with the quality of screening when administered by staff, who may change the wording of validated screening questions in an effort to hasten the process or reduce perceived patient discomfort …”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with those of previous studies using self-administered screening, which typically produces more accurate reporting among patients with stigmatized conditions. [53][54][55] Our findings could also reflect problems with the quality of screening when administered by staff, who may change the wording of validated screening questions in an effort to hasten the process or reduce perceived patient discomfort. 56,57 Screening rates were similar for alcohol and drug use, likely reflecting the fact that most clinics administered the alcohol and drug screenings simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…All patients indicated that the self-administered screening was highly acceptable, consistent with previous findings [33,49]. Prior research has provided evidence for patient acceptability of a self-administered TAPS format [33,49,50], while our results build on those findings to show the utility of multiple modes of self-administration (online patient portal and in-clinic tablet) in meeting the needs of different patient populations. Both patients and providers felt that having both options available allowed for more flexibility in administration and an increased likelihood of completion.…”
Section: Discussionsupporting
confidence: 88%
“…In the universal screening survey, probable OUD was screened for using items adapted from the myTAPS screener, a self-administered version of the National Institute on Drug Abuse Tobacco, Alcohol, Prescription medication and other Substance use (TAPS) screener [37]. When used for screening problematic heroin and prescription opioid use, the original TAPS instrument had sensitivity of 0.77 and 0.73 and specificity of 0.99 and 0.98, respectively.…”
Section: Methodsmentioning
confidence: 99%